P491 Efficacy and safety of upadacitinib for the treatment of fistulas and fissures in patients with Crohn's disease. (30th January 2023) - Colombel, J F; Irving, P; Rieder, F; Panaccione, R; Schwartz, D; Hayashi, R; Zhu, X; Lacerda, A P; Dubcenco, E; Marced, E; Hecht, P; Feng, T; et al.
Abstract: Background: Intestinal and perianal fistulas and fissures are associated with significant morbidity and decreased quality of life in patients with Crohn's disease (CD). We evaluated rates of fistula and fissure improvements with upadacitinib (UPA), an oral selective Janus kinase inhibitor, in patients with CD who had fistulas or fissures at baseline in phase 3 induction and maintenance trials. Methods: In the U-EXCEL (NCT03345849) and U-EXCEED (NCT03345836) phase 3 induction trials, patients with moderate-to-severe CD were randomized to UPA 45 mg once daily (QD) or placebo (PBO) for 12 weeks. Patients who achieved clinical response after 12 weeks of induction were eligible for U-ENDURE (NCT03345823) and rerandomized to UPA 30 mg QD, UPA 15 mg QD, or PBO for an additional 52 weeks of maintenance treatment. Fistula activity was assessed by presence of external openings and draining upon gentle compression. Presence of perianal fissures was also assessed. The proportion of patients with external closure of fistula openings, complete resolution of draining, and ≥ 50% reduction in draining was recorded at weeks 12 and 52. Endpoints were analyzed using non-responder imputation. Results: Of 1021 enrolled patients, 143 patients had fistulas (124 [86.7%] perianal; 19 [13.3%] enterocutaneous) and 54 patients had perianal fissures at baseline. The proportion of patients who achieved external closure of fistula openings was higher with UPA vs PBO at week 12 (Fig 1A) and at week 52 (Fig 2A). The proportion of patients who achieved complete resolution of draining and ≥ 50% reduction in draining was higher with UPA vs PBO at week 12 (Fig 1B and 1C) and at week 52 (Fig 2B and 2C). A higher proportion of patients achieved complete resolution of fissures with UPA vs PBO at week 12 (Fig 1D) and at week 52 (Fig 2D). At weeks 12 and 52, a higher proportion of patients with fistulas treated with UPA vs PBO achieved clinical remission and endoscopic response (Fig 1E and 2E). Rates of adverse events (AEs), serious AEs, or AEs leading to study drug discontinuation were similar in UPA groups compared with PBO during the induction and maintenance periods. Rates of abscess formation were 1.8% with UPA 45 mg and 6.8% with PBO at week 12, and 3.0% with UPA 30 mg, 6.4% with UPA 15 mg, and 2.5% with PBO at week 52. Conclusion: Among patients with CD complicated with fistulas and/or fissures at baseline, UPA treatment led to higher rates of external closure of fistula openings, resolution of draining, and healing of fissures, along with clinical remission and improvements in luminal disease compared with PBO. No new safety concerns were identified.